2018
DOI: 10.1103/physreva.98.042301
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement protection via periodic environment resetting in continuous-time quantum-dynamical processes

Abstract: The temporal evolution of entanglement between a noisy system and an ancillary system is analyzed in the context of continuous-time open quantum system dynamics. Focusing on a couple of analytically solvable models for qubit systems, we study how Markovian and non-Markovian characteristics influence the problem, discussing in particular their associated entanglement-breaking regimes. These performances are compared with those one could achieve when the environment of the system is forced to return to its input… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 160 publications
(306 reference statements)
0
6
0
Order By: Relevance
“…Therefore entanglement can eventually reach zero at the special times (or time intervals) where the process becomes EB, and then reappear again (see the solid blue line in Figure 2c). In [13] it has been shown that the EB properties of a non-Markovian evolution can be manipulated by properly acting on the environment via periodic resetting of its initial state. This is formally realized by dividing the temporal axis into a collection of time intervals I n = [t n , t n+1 ) of equal length τ = t n+1 − t n with t 0 = 0, and by defining a new family of mappings {Φ Figure 2c we report a case study regarding a qubit S interacting with a bosonic reservoir at zero temperature characterized by a Lorentzian spectral density.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore entanglement can eventually reach zero at the special times (or time intervals) where the process becomes EB, and then reappear again (see the solid blue line in Figure 2c). In [13] it has been shown that the EB properties of a non-Markovian evolution can be manipulated by properly acting on the environment via periodic resetting of its initial state. This is formally realized by dividing the temporal axis into a collection of time intervals I n = [t n , t n+1 ) of equal length τ = t n+1 − t n with t 0 = 0, and by defining a new family of mappings {Φ Figure 2c we report a case study regarding a qubit S interacting with a bosonic reservoir at zero temperature characterized by a Lorentzian spectral density.…”
Section: Resultsmentioning
confidence: 99%
“…that holds for a generic (time-independent) unitary conjugation U. Equation (19) can be easily verified by noticing that given the semigroup Φ t generated by L, and the semigroup Φ t generated by L = U −1 • L • U, the two are connected as in (18) by setting V t = U −1 and U t = U.…”
Section: A Preliminary Observationsmentioning
confidence: 92%
“…Since it defines the maximum time interval on which we are guaranteed to have some entanglement between A and B under the evolution (1), we shall refer to τ ent as the "entanglement survival time" (EST) of the selected dynamical process. Notice however that if the maps {Φ t,0 } t≥0 exhibit a strong non-Markovian character inducing a significative back-flow of information into the system temporal evolution [15][16][17][18][19], nothing prevents the possibility that entanglement between A and B will re-emerge at some time t greater than τ ent . The same effect however cannot occur in the case of Markovian or weakly non-Markovian models for which instead one has…”
Section: Maximum Entanglement Survival Timementioning
confidence: 99%
See 1 more Smart Citation
“…A general noise results in the purity degradation (the state becomes mixed) and entanglement degradation (the state becomes separable if the noise is strong enough [37,47]). To fight with reasons (i) and (ii), one resorts to the most robust entangled states [37,48] or interventions in the noisy dynamics [49]. Reason (iii) significantly affects the performance of entanglement-enabled protocols because any such protocol relies on a properly prepared (pure) entangled state [1, [25][26][27].…”
Section: Introductionmentioning
confidence: 99%